OHS Information System (Occupational Health and Safety) In PT. United Tractors Tbk, Site-Satui Mobile Web Based - Maya Gian Sister; Agustian Noor; Khairul Anwar Hafizd (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
Medical Check-Up (MCU) is a health check Overall, which is carried out to monitor the health of employees at PT United Tractors Tbk, Site Satui, which is expected from this examination to detect a disease or health problem from an early age, PT United Tractors Tbk, Site-Satui is one company that requires a system that can monitor health. and the safety of employees at work. Therefore, an occupational health and safety (OHS) system was built, which is expected to assist in monitoring the results of medical check-ups for an employee (MCU), sending health information, monitoring employee health level charts. This occupational health and safety system were built using the method prototype, made using the programming language Hypertext Preprocessor (PHP) and the MySQL database, designed using Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and Flowcharts.